Evaluasi Kebijakan Pemberian Bantuan Produktif Usaha Mikro (BPUM) Kepada Pelaku Usaha Mikro Di Kabupaten Sekadau - Etika Haryati; Zulkarnaen Zulkarnaen; Pardi Pardi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Micro, Small, and Medium Enterprises (MSMEs/ known as UMKM) playastrategic role in driving national economic growth, particularly in job creationandequitable development. To sustain the operations of MSMEs during the COVID- 19 pandemic, the government launched the Productive Assistance Program for Micro Enterprises (BPUM). This study aims to analyze and evaluate theimplementation outcomes of the BPUM program in Sekadau Regency in 2021. The research adopts a descriptive method with a qualitative analytical approach. Data were collected through interviews and documentation techniques. Thefindings indicated that, overall, the BPUM program significantly supported micro- entrepreneurs in maintaining their business operations. However, several challenges were identified during its implementation, including unequal distribution, inadequate verification and field monitoring, and limited publicoutreach. The evaluation, based on William N. Dunn’s public policy evaluationcriteria, such as effectiveness, efficiency, adequacy, equity, responsiveness, andappropriateness, revealed that effectiveness, equity, and target accuracy have yet to reach optimal levels. The identified issues stemmed from internal factors suchas limited human resources, insufficient funding, and the absence of fieldverification, as well as external factors such as limited access to informationandthe low quality of human resources among the community. This studyrecommends enhancing human resource capacity, strengthening budget allocations, improving verification and monitoring mechanisms, and intensifyingpublic outreach efforts to ensure the future success of the BPUMprogram.